The Impact of Labor Intermediation and Training in High Informality Contexts. Evidence from Paraguay. - Nicolás Campos; Miguel Chalup; Oscar A. Mitnik; Manuel Urquidi (Institute of Labor Economics (IZA), 2024)
We provide quasi-experimental estimates of the impact of reforming public training programs offered in Paraguay on formal employment. The Programa de Apoyo a la Inserción Laboral (PAIL) revamped training program design in the country by offering courses aligned with the needs of the private sector, enhancing non-cognitive skills, and combining practical work within companies with classroom training. We combine administrative records—which contain detailed information on the employment history and characteristics of all formal workers in Paraguay—with an empirical strategy based on extensions of difference-in-differences models and synthetic difference-in-differences. We find that the probability of obtaining formal employment for women and men increases by 11 percentage points. Even two years after participating, the program has a lasting impact on women, an aspect not observed for men. Additionally, the program's impact is positive only in the metropolitan area of Asunción; the program is less effective in areas far from the urban center, especially for men. The observed results suggest that supply-side interventions are ineffective if no formal jobs are available for the beneficiaries.
Keywords: J24; J38; J68; 330; public training programs; active labor market policies; formal employment